2004
DOI: 10.1002/chin.200419032
|View full text |Cite
|
Sign up to set email alerts
|

Alkylative Reduction of Titanium(IV) Isopropoxide with EtMgBr: Convenient Method for the Generation of Subvalent Titanium Alkoxide Reagents and Their Reactivity in Pinacol Coupling Reactions.

Abstract: A reagent combination of Ti(OiPr)4 and ethylmagnesium bromide generates low valent Ti(OiPr)3 which is readily used to transform carbonyl compounds into the corresponding pinacols. -(MATIUSHENKOV, E. A.; SOKOLOV, N. A.; KULINKOVICH*, O. G.; Synlett 2004, 1, 77-80; Dep. Org. Chem., Belarus State Univ., Minsk 220050, Belarus; Eng.) -Mais 19-032

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…D 2 O quenching of the reaction mixture after epoxide 6h reduction gave no deuterated product, which showed that the radical formation was followed by HAT. Reaction in THFd 8 gave no deuteration product as well. Finally, we detected partial incorporation of the isotopic label in 7h when titanium alkoxide 16 was used instead of Ti(OiPr) 4 .…”
mentioning
confidence: 97%
“…D 2 O quenching of the reaction mixture after epoxide 6h reduction gave no deuterated product, which showed that the radical formation was followed by HAT. Reaction in THFd 8 gave no deuteration product as well. Finally, we detected partial incorporation of the isotopic label in 7h when titanium alkoxide 16 was used instead of Ti(OiPr) 4 .…”
mentioning
confidence: 97%